An Examination of the Role of Government in Making Hydroelectricity Energy Accessible in Remote Areas of Uganda: a Case Study of Kisoro District. - Rhona Atamba (Uganda Christian University, 2025)
This study examines the impact of internal control systems on the financial performance of the Ministry of Education and Vocational Training in Zanzibar. The objectives were to: (1) assess the effectiveness of the existing internal control mechanisms, (2) evaluate their influence on financial performance, and (3) identify challenges hindering their implementation. Employing a descriptive research design, the study targeted a population of 150 employees across various departments, from which a sample of 100 respondents was selected using stratified random sampling. Data were collected through structured questionnaires and document analysis. Quantitative data were analyzed using descriptive statistics and regression analysis, while qualitative data underwent thematic analysis. Findings revealed that while internal control mechanisms such as segregation of duties and authorization procedures exist, their effectiveness is compromised by inconsistent application and lack of regular monitoring. Specifically, the study found that: (1) the control environment is weakened by inadequate management support, (2) risk assessment processes are underdeveloped, and (3) control activities are not uniformly enforced across departments. Consequently, these deficiencies adversely affect the Ministry's financial performance. The study concludes that strengthening internal control systems is imperative for enhancing financial accountability and performance. It recommends: (1) regular controls. Implementing these measures is expected to improve resource utilization and financial transparency within the Ministry.
Undergraduate dissertation